The VegPlate for sports: A plant-based food guide for athletes - Baroni, L.; Pelosi, E.; Giampieri, F.; Battino, M. (Nutrients, 2023)
Background: Nutrition strategies improve physiological and biochemical adaptation to training, facilitate more intense workouts, promote faster recoveries after a workout in anticipation of the next, and help to prepare for a race and maintain the body`s hydration status. Although vegetarianism (i.e., lacto-ovo and veganism) has become increasingly popular in recent years, the number of vegetarian athletes is not known, and no specific recommendations have been made for vegetarian dietary planning in sports. Well-planned diets are mandatory to obtain the best performance, and the available literature reports that those excluding all types of flesh foods (meat, poultry, game, and seafood) neither find advantages nor suffer from disadvantages, compared to omnivorous diets, for strength, anaerobic, or aerobic exercise performance; additionally, some benefits can be derived for general health. Methods: We conceived the VegPlate for Sports, a vegetarian food guide (VFG) based on the already-validated VegPlate facilitating method, designed according to the Italian dietary reference intakes (DRIs). Results: The VegPlate for Sports is suitable for men and women who are active in sports and adhere to a vegetarian (i.e., lacto-ovo and vegan) diet, and provides weight-based, adequate dietary planning. Conclusions: The VegPlate for Sports represents a practical tool for nutrition professionals and gives the possibility to plan diets based on energy, carbohydrate (CHO), and protein (PRO) necessities, from 50 to 90 Kg body weight (BW).